Percutaneous closure of mitral paravalvular leaks: Focus on imaging and technique - Eeckhout, Eric; Girod, Grégoire; Muller, Olivier; Roguelov, Christan; Iglesias, Juan-Fernando; Delabays, Alain (SA Heart Journal, 2017)
Symptomatic prosthetic paravalvular leakage is a rare clinical condition occurring in up to 5% of patients after valve surgery. Symptoms include haemolytic anaemia, heart failure or both. Leaks tend to be more common in the mitral compared to the aortic position. Three dimensional transoesophageal echocardiography (3D TOE) is essential prior and during percutaneous leak closure. This imaging technique allows to qualify and quantify the leak and to judge feasibility of a percutaneous approach. It also enables the choice of the most appropriated closure device prior to intervention. During the procedure, 3D TOE guides adequate crossing of the leak and device deployment. It also fi nally allows assessment of the acute procedural result. Percutaneous closure should be considered as the fi rst choice therapy if closure is judged feasible based on 3D TOE assessment. This procedure is currently performed in a limited number of patients by relatively few operators and is characterised by a long learning curve. Currently, literature data are scarce and reported acute procedural success is roughly around 70 to 80%. Intervention is mostly performed with vascular plugs or ventricular septum defect closure devices. Recently, dedicated implants have been made available. Their role has been limited to hybrid procedures from a transapical retrograde approach.